The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1975
DOI: 10.1364/ao.14.001592
|View full text |Cite
|
Sign up to set email alerts
|

Space-invariant achromatic grating interferometers: theory

Abstract: A general analysis of an n-grating interferometer under various conditions of illumination is presented, where n = 1,...,4. Conditions for fringe localization and effects of misalignment are given. The lesser known phenomenon of the imaging of a grating by a second grating is described from which the fringe forming capacity of multiple-grating interferometers stems; this can occur regardless of the coherence of the source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…3, taking advantage of the well-known tendency of SFHe to flow up walls and coat the inside of its container. Note that the exact horizontality of the beam is not crucial, thanks to the incident-angle independence of the Mach-Zehnder arrangement [6]. …”
Section: Beammentioning
confidence: 99%
“…3, taking advantage of the well-known tendency of SFHe to flow up walls and coat the inside of its container. Note that the exact horizontality of the beam is not crucial, thanks to the incident-angle independence of the Mach-Zehnder arrangement [6]. …”
Section: Beammentioning
confidence: 99%
“…The analysis by Leith et al [2][3][4] was based on a first-order approximation of the transfer function of free space. It was found that nonlocalized fringes form for polychromatic plane-wave illumination at any angle e and localized fringes form for extended sources (multiple illumination angles), regardless of source spectral bandwidth (color content).…”
Section: Previous Work On the Parallel Two-grating Interferometermentioning
confidence: 99%
“…With an achromatic grating interferometer [3][4] for example, the lateral position of a point radiator is mapped into the spatial frequency of a sinusoidal fringe pattern. The moving scatterers would therefore create fringe patterns of varying frequencies.…”
Section: %mentioning
confidence: 99%